Peritoneal Metastatic Cancer Stem Cells of Gastric Cancer with Partial Mesenchymal-Epithelial Transition and Enhanced Invasiveness in an Intraperitoneal Transplantation Model - Xiao-Hai Song; Xin-Zu Chen; Xiao-Long Chen; Kai Liu; Wei-Han Zhang; Xian-Ming Mo; Jian-Kun Hu (Gastroenterology Research and Practice, 2020)
Objectives. This preliminary study is aimed at enriching and isolating peritoneal metastatic cancer stem cells (pMCSCs) of gastric cancer and assessing their epithelial-mesenchymal transition (EMT) phenotype and invasiveness. Methods. Cancer stem cells of human gastric cancer (CSC-hGC) were previously isolated and transfected with green fluorescent protein and luciferase genes to validate the mouse model of peritoneal metastasis established via transplantation. The first and second generations ([G1] and [G2], respectively) of pMCSCs were isolated from intraperitoneally transplanted CSC-hGC (pMCSC-tGC) by spherical culture. CSC and EMT-related markers and regulators in the two generations of intraperitoneally transplanted tumors were examined by immunohistochemistry, immunofluorescence staining, and quantitative PCR. Cell mobility was examined by a transwell assay. Results. The nude mouse model of intraperitoneally transplanted CSC-hGC was successful in establishing sequential formation of peritoneal tumors and enrichment of pMCSCs. CD44 and CD54 were consistently expressed in the two generations of transplanted tumors. In vitro cell (migration) assays and immunocytofluorescence assays showed that in pMCSC-tGC[G2], E-cad, Survivin, and Vimentin expression was stable; α-SMA expression was decreased; and OVOL2, GRHL2, and ZEB1 expression was increased. PCR analysis indicated that in pMCSC-tGC[G2], the mRNA expression of E-cad, α-SMA, MMP9, MMP2, and Vimentin was downregulated, while that of ZEB1, OVOL2, and GRHL2 was upregulated. In vivo tumor (homing) assays and immunohistochemical assays demonstrated that in pMCSC-tGC[G2], E-cad and Snail were upregulated, while α-SMA was downregulated. The numbers of migrated and invaded pMCSC-tGC[G1] and pMCSC-tGC[G2] were significantly higher than those of CSC-hGC in migration and invasion assays. Conclusions. pMCSCs might be a specific subpopulation that can be sequentially enriched by intraperitoneal transplantation. pMCSCs exhibited a tendency towards partial mesenchymal-epithelial transition, enhancing their invasiveness during homing and the formation of peritoneal tumors. However, these preliminary findings require validation in further experiments.